A Study of CO2 Methanation over Ni-Based Catalysts Supported by CNTs with Various Textural Characteristics - Yanyan Feng; Wen Yang; Wei Chu (International Journal of Chemical Engineering)
This work studied the influence of textural characteristics of CNTs on catalytic performance of Ni/CNTs for CO2 methanation. The CNTs supports were prepared by chemical vapor deposition method using Ni/MgO catalysts, and acetonitrile and ethanol were used as carbon sources, respectively. The Ni/CNTs catalysts were prepared via impregnation method and characterized by X-ray diffraction (XRD), N2 adsorption/desorption, and temperature-programmed reduction (H2-TPR) techniques. The results indicated that the textural characteristics of CNTs supports significantly impacted on the catalytic performance of Ni/CNTs. The catalyst Ni/CNTs-E (CNTs using ethanol as carbon source) had good reducibility, high specific surface area, and moderate defects, resulting in higher CO2 conversion and CH4 yield, followed by Ni/CNTs-C (commercial CNTs) and Ni/CNTs-A (CNTs using acetonitrile as carbon source). Based on Arrhenius formula, activation energies of the catalysts were calculated and were found decreased for Ni/CNTs-A and Ni/CNTs-E.